2007
DOI: 10.1128/mcb.00083-07
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses of Transcription Factor Binding, Histone Acetylation, and Gene Expression Reveal Mechanistically Distinct Classes of Estrogen-Regulated Promoters

Abstract: To explore the global mechanisms of estrogen-regulated transcription, we used chromatin immunoprecipitation coupled with DNA microarrays to determine the localization of RNA polymerase II (Pol II), estrogen receptor alpha (ER␣), steroid receptor coactivator proteins (SRC), and acetylated histones H3/H4 (AcH) at estrogen-regulated promoters in MCF-7 cells with or without estradiol (E2) treatment. In addition, we correlated factor occupancy with gene expression and the presence of transcription factor binding el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
133
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 50 publications
(73 reference statements)
21
133
2
2
Order By: Relevance
“…However, the GME appears to be equally active with both endogenous and synthetic reporter genes Szapary et al, 1992;Collier et al, 1996). Furthermore, it is clear from microarray studies that endogenous genes yield a spectrum of responses that resist generalization (Mittelstadt and Ashwell, 2003;Rogatsky et al, 2003;Donn et al, 2007;Kininis et al, 2007). Therefore, the present results establish that various factors can unequally alter the transcription properties of PR vs. GR in a model system that most likely is recapitulated by some endogenous regulated genes.…”
Section: Discussionmentioning
confidence: 50%
“…However, the GME appears to be equally active with both endogenous and synthetic reporter genes Szapary et al, 1992;Collier et al, 1996). Furthermore, it is clear from microarray studies that endogenous genes yield a spectrum of responses that resist generalization (Mittelstadt and Ashwell, 2003;Rogatsky et al, 2003;Donn et al, 2007;Kininis et al, 2007). Therefore, the present results establish that various factors can unequally alter the transcription properties of PR vs. GR in a model system that most likely is recapitulated by some endogenous regulated genes.…”
Section: Discussionmentioning
confidence: 50%
“…With the activation of cell signaling pathway, histone acetylation levels of nuclear receptors (such as ER, GR, RAR, VDR) target genes are significantly increased, thus activating gene transcription upon hormone induction. Genomic analyses of transcription factor binding indicate a remarkable positive correlation between the recruitment of Pol II at the promoters of E 2 -stimulated genes and the acetylated histone levels (Kininis et al, 2007). Using a well-established ACI rat model, Kristy R et al identified morphological and epigenetic changes in the mammary gland tissue after exposure to constitutively elevated estrogen levels, and found that progressive hyperproliferative changes were paralleled by epigenetic disturbances, which demonstrates that the hyperacetylation of histone induced by estrogen has a significant role in the early stage of breast cancer development (Kutanzi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is an important factor promoting cell proliferation in estrogen receptor (ER) positive breast cancer, which is associated with abnormal changes in acetylation levels in current study (Kininis et al, 2007). Estrogen may affect the acetylation levels of histones or nonhistones of oncogenes, thus boost oncogene expression, tumor cell transformation, accelerate proliferation and inhibit apoptosis.…”
Section: Introductionmentioning
confidence: 86%
“…However, recently the FASEB steroid signaling work group suggested that "membrane-initiated steroid signaling" and "nuclear-initiated steroid signaling" are more appropriate terminologies (Hammes and Levin, 2007). The nuclear-effects on a variety of tissues that involves gene stimulation as well as gene repression (Herbison, 1998, Couse and Korach, 1999, Nilsson et al, 2001, Stossi et al, 2006, Kininis et al, 2007. In general, this "classical" signaling pathway of estrogen involves steroid-dependent formation of nuclear estrogen receptor homo-or heterodimers and the subsequent binding of this complex with a unique DNA sequence known as an estrogen response element (ERE), in E2-responsive gene promoters (O'Malley and Tsai, 1992, Muramatsu and Inoue, 2000, Gruber et al, 2004.…”
Section: Nuclear-initiated Signaling Of E2mentioning
confidence: 99%